The Number of Chronic Conditions and Domain-Specific Movement Behaviours Among People Aged ≥15 Years: Findings from the 2019 Serbian National Health Survey - Dragana Jovic; Jadranka Plavsic; Shihab Aldin Ahmad Al-Riyami; Maja Vukovic; Veroslava Stankovic; Jasmina Pluncevic Gligoroska (Healthcare, 2026)
Background/Objectives: Previous studies have linked chronic conditions and multimorbidity to lower physical activity, but evidence across individual movement behaviours remains limited. We examined associations between the number of self-reported chronic diseases and conditions and transport-related walking, leisure time physical activity, muscle-strengthening activity and sedentary behaviour among people aged ≥15 years in Serbia. Methods: Nationally representative 2019 Serbian National Health Survey data were analysed (n = 13,076 with complete information on 17 conditions). Complex sample logistic regression models were sequentially adjusted for sociodemographic characteristics, body mass index, functional mobility and self-rated health. Additional analyses assessed linear trends and departures from linearity using all covariates except self-rated health. Results: Overall, 51.4% reported no condition, 18.0% one and 30.6% two or more. All outcomes were associated with condition status before adjustment, but most associations were attenuated after including functional mobility. After full adjustment, an overall association remained only for muscle-strengthening activity on